Knockdown of POSTN Inhibits Osteogenic Differentiation of Mesenchymal Stem Cells From Patients With Steroid-Induced Osteonecrosis - Han, Lizhi; Gong, Song; Wang, Ruoyu; Liu, Shaokai; Wang, Bo; Chen, Guo; Gong, Tianlun; Xu, Weihua (Frontiers in Cell and Developmental Biology, 2020)
Steroid-induced osteonecrosis of femoral head (SONFH) is a common and serious complication caused by long-term and/or excessive use of glucocorticoids (GCs). The decreased activity and abnormal differentiation of bone marrow mesenchymal stem cells (BMSCs) are considered to be one of the major reasons for the onset and progression of this disease. Periostin (POSTN) is a matricellular protein which plays an important role in regulating osteoblast function and bone formation. Sclerostin (SOST) is a secreted antagonist of Wnt signaling that is mainly expressed in osteocytes to inhibit bone formation. However, the exact role of POSTN and SOST in SONFH has not been reported yet. Therefore, we detected the differential expression of POSTN and SOST in BMSCs of SONFH Group patients, and Control Group was patients with traumatic ONFH (TONFH) and developmental dysplasia of the hip (DDH). Furthermore, we used lentiviral transfection to knockdown POSTN expression in BMSCs of patients with SONFH to study the effect of POSTN knockdown on the SOST expression and osteogenic differentiation of BMSCs. The results indicated that the endogenous expression of POSTN and SOST in BMSCs of SONFH Group was upregulated, compared with Control Group. POSTN was upregulated gradually while SOST was downregulated gradually at days 0, 3, and 7 of osteogenic differentiation of BMSCs in Control Group. Contrarily, POSTN was gradually downregulated while SOST was gradually upregulated during osteogenic differentiation of BMSCs in SONFH Group. This could be due to increased expression of SOST in BMSCs, which was caused by excessive GCs. In turn, the increased expression of POSTN in BMSCs may play a role in antagonizing the continuous rising of SOST during the osteogenic differentiation of BMSCs in patients with SONFH. POSTN knockdown significantly attenuated osteo-specific gene expression, alkaline phosphatase activity, and calcium nodule formation in vitro; thus inhibiting the osteogenic differentiation of BMSCs in patients with SONFH. Besides, POSTN knockdown upregulated SOST expression, increased GSK-3β activity, and downregulated β-catenin. These findings suggest that POSTN have an essential role in regulating the expression of SOST and osteogenic differentiation of BMSCs in patients with SONFH, and POSTN knockdown suppresses osteogenic differentiation by upregulating SOST and partially inactivating Wnt/β-catenin signaling pathway. Therefore, targeting POSTN and SOST may serve as a promising therapeutic target for the prevention and treatment of SONFH.